On Hartwick's Rule - Dekrét, Anton (O regule Hartwicka, 2009)
In this paper two mathematical versions of the Hartwick's rule are described. The first is connected with optimal control models, and price variables are used. The other one is formulated without price variables in control models without optimization. It is shown that the first formulation can be used also in general control models.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 57-61